Atributos físicos de Latossolo cultivado com cana-de-açúcar e adubado com dejetos de animais de criação intensiva - Gomides, Juliana do Nascimento (2009)
The cultivation of sugarcane is in strong expansion in the Cerrado region, requiring management techniques to maintain the soil physical quality. The use of animal s manure from intensive husbandry constitutes an alternative to reduce the physical degradation of the poor soil use due to lower cost with chemical fertilizations and, mostly, making possible the sustainable use of manures that present great polluting potential. Thus, this research analyzed the use of manures in nature or composted as alternatives to minimize the negative impacts in the soil, from sugarcane cultivation, evaluating its effect in the soil s structure and other physical attributes. The area of the research was located in the Farm of Cia Mineira of Sugar and Alcohol, county of Uberlândia-MG. The experimental design was randomized blocks, in a 5x2x2 factorial, with split plots in space, corresponding to five types of fertilization: chicken manure, turkey manure, cattle manure, organic compost and the control, constituted of mineral fertilizer for the sugarcane plants, all of them combined, or not, with gypsum, previously mixed to the fertilizers and applied in the furrow; at two depths and two distinct times of the year, at the rainy and dry seasons. Soil samples were collected in January and July, in the depths of 0-25 cm and 25-50 cm, and were evaluated for dispersed clay in water, flocculation degree, aggregate stability in water, geometric average diameter, soil organic matter, soil density, microporosity, macroporosity and total porosity according of methodology described by Embrapa (1997). The data were submitted to the analysis of variance and the averages of the factors compared by the Tukey test at 0.05 of significance. It was observed that the different types of manures affected the soil physical attributes in distinct ways. The presence of gypsum, mixed to the different types of organic fertilizer, made possible a greater efficiency of these in the recovery of the majority of the analyzed physical attributes, and the greatest effect was observed for the depth of 25-50 cm in the soil. Among the types of organic fertilizer used, cattle manure mixed with or without gypsum was the one contributing the most to increase total porosity and to reduce soil density. The chemical fertilizer negatively affected dispersed clay in water and, consequently, the reduction of the soil flocculation degree. However, for the other fertilizers analyzed, the dispersed clay in water showed value reductions in the dry season, with greater movement of the clay in soil columns. The greatest values of geometric average diameter and soil organic matter were observed in the rainy season, while the presence of gypsum mixed to fertilizer favored the formation of greater aggregates in the depth of 25-50 cm. The soil physical properties, for the attributes evaluated, varied distinctly between the rainy and the dry period of the year, reflecting the importance of moisture in the soil.